1987
DOI: 10.1136/bmj.295.6606.1098
|View full text |Cite
|
Sign up to set email alerts
|

Asphyxiation by a child's dummy.

Abstract: She was followed up regularly for almost two years and showed no signs of relapse. She stopped taking antithyroid drugs several times and suffered brief relapses of hyperthyroidism, but without any psychosis. CommentHyperthyroidism commonly presents with mental changes such as irritability and anxiety, but psychotic symptoms like hallucination and delusion are rare. The review by Ellis and Mellsop shows that de C1erambault's syndrome is also rare.Our case satisfied all the criteria of the syndrome, but it did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A careful review of the literature revealed nine similar cases since 1966 [1, 2, 4±10], summarised in Table 1 along with our own case. The possibility of non-accidental injury was actively considered in several cases [1,2,4,7] but proven in none. Millunchick and McArtor [8] concerned a makeshift paci®er composed of a bottle teat, plastic collar and tape.…”
Section: Discussionmentioning
confidence: 99%
“…A careful review of the literature revealed nine similar cases since 1966 [1, 2, 4±10], summarised in Table 1 along with our own case. The possibility of non-accidental injury was actively considered in several cases [1,2,4,7] but proven in none. Millunchick and McArtor [8] concerned a makeshift paci®er composed of a bottle teat, plastic collar and tape.…”
Section: Discussionmentioning
confidence: 99%
“…This case illustrates the need for ventilation holes in dummies, without such holes this child may well have asphyxiated. A case of asphyxiation caused by a dummy has been described (Clayton et al,, 1987). At that time ventilation holes in the flange of the dummy were not mandatory.…”
Section: Discussionmentioning
confidence: 99%